Gender-specific differences in geographical mobility: Evidence from Ghana - Emmanuel Orkoh; Victor Stolzenburg (World Trade Organization (WTO), 2020)
The gains from trade depend on the reallocation of resources, including labour, across firms and sectors. However, workers are unlikely to be fully mobile since there are barriers to sectoral and geographical mobility due to social reasons such as family or existing private and professional networks. If these barriers depend on specific characteristics of workers, such as education, gender or race, this has important implications for inequality. In this note we examine gender-specific differences regarding geographical mobility in Ghana. Using survey data from the 2017 Ghana Living Standard Survey, we find that while men and women are equally likely to migrate, men are much more likely to move for economic reasons. Women on the other hand move predominantly for social reasons such as marriage. This is supported by both indicated reasons for migration and indirect evidence. For instance, men are more likely to be employed, send higher and more frequently remittances, and target regions that offer better employment prospects. These stylized facts suggest that Ghanaian men can more easily adjust to trade shocks than Ghanaian women. While we cannot infer from this evidence what determines the differences in geographical mobility between men and women, we can infer that men are more likely to benefit from a trade-induced expansion of exporting sectors and firms and are less likely to be hurt by a tradeinduced contraction of import-competing sectors and firms.
Keywords: J16; J61; 330; gender inequality; mobility; gains from trade